The Design of Juan Bautista Vázquez ‘the Elder’ for the Processional Monstrance of Tunja (Colombia) (BSAA arte, 2019)
This article expands the corpus of drawings by Juan Bautista Vázquez ‘the Elder’ that I had the pleasure of inaugurating in 1983 on the pages of BSAA. A new document shows the appearance of the former processional monstrance of Tunja (Colombia), and proves how far its design was indebted to Sevillian liturgical silverwork, whose Renaissance multi-storey baldachin-structures are translated into gilded wood in Vázquez’s work. Quite useful is the recommendation made to the sculptor, asking him to send the monstrance dismantled inside boxes weighing no more than five arrobas, so that they could be easily transported on canoes through the Magdalena River.
Keywords: Renaissance; Juan Bautista Vázquez the Elder; Gil V´ázquez; processional monstrance; river transportation; Tunja (Colombia)